A comparative evaluation of two irrigating solutions combination effectiveness on apical sealing of different root canal sealers - Godelatia Jesslyn; Bernard Ongki Iskandar; Tien Suwartini; F Loes Djimahit Sjahruddin (Faculty of Dentistry, Universitas Trisakti, 2023)
Background: Root canal irrigants play an essential role in removing the smear layer, pulp tissue, and microorganisms in the root canal system. The irrigation solution can remove the smear layer, which can interfere with the bond between the sealers. As a result of sealer penetration into dentin tubules following smear layer removal, an apical seal was obtained. One of the most recent innovations in root canals consists of a combination of silver citrate (BioAKT, New Tech Solution, Brescia, Italy) and chlorhexidine-ethylenediaminetetraacetic acid (CHX-EDTA; SmearOFF, Vista Dental, Racine, USA). These irrigants were used as the final irrigant for root canal disinfection. Epoxy sealers (AH26, Dentsply Maillefer, Ballaigues, Switzerland) and bioceramic sealers (ceraseal, Meta Biomed Co., Cheongju, Korea) have excellent adhesive properties and sealing ability and are commonly used as obturation materials. Objective: The aim of this study was to compare the effectiveness of a root canal combination irrigant between silver citrate and CHX-EDTA on the apical sealing ability of epoxy sealer and bioceramic sealer. Materials and Methods: Forty extracted mandible single-root premolars were used in this study. The root canal preparation was done with a rotary instrument until no. 30.06. Irrigation was performed using 5.25% NaOCl between instrumentations. The final irrigant and sealers were Group I: BioAKT + ceraceal; Group II: BioAKT + AH26; Group III: SmearOFF + ceraceal; and Group IV: SmearOFF + AH26. Obturation was then performed using the warm vertical compaction technique. The sealing ability of endodontic sealers was evaluated using the dye penetration method under the magnification of the stereomicroscope. The data were statistically analyzed using a two-way analysis of variance (ANOVA) (SPSS, IBM, USA). Results: No significant difference (P > 0.05) was observed between the four experimental groups. Conclusion: Both combination irrigants and sealers showed comparable effectiveness in smear layer removal and a similar sealing ability.